Falls in older adults: a practical approach - Pereira, Cristiana Borges; Kanashiro, Aline Mizuta Kozoroski (Arquivos de Neuro-Psiquiatria, 2022)
Background: Falls are a major problem in public health since they are an important cause of morbidity and mortality. To evaluate the risk of fall and prescribe preventive interventions may be a challenging task. Objectives: The objectives of this study are to summarize the most relevant information on the topic “falls in the elderly” and to give a critical view and practical clinical approach on this topic. Methods: In March 2022, a search of Pubmed database was performed, using the terms “fall elderly”, fall prevention”, “fall risk”, with the following parameters: five years, review, systematic review, meta-analysis, practice guidelines. Results: There are several risk factors for falls that can be grouped in different areas (psychosocial, demographic, medical, medication, behavioral, environmental). The clinical evaluation of an older adult prone to falls must include identification of risk factors through history and examination and identification of risk of falls through an assessment tool such as gait velocity, functional reach test, timed up and go, Berg balance test, and miniBEST test. Fall prevention strategies can be single or multiple, and physical activity is the most cited. Technology can be used to detect and prevent falls. Conclusion:  A systematic approach to the older patient in risk of falls is feasible and may impact fall prevention.
Keywords: Accidental Falls; Aged